The determinants of venture capital funding: evidence across countries - Jeng, Leslie A.; Wells, Philippe C. (Journal of Corporate Finance, 2000)
This paper analyses the determinants of venture capital for a sample of 21 countries. In particular, we consider the importance of initial public offerings (IPOs), gross domestic product (GDP) and market capitalization growth, labor market rigidities, accounting standards, private pension funds, and government programs. We find that IPOs are the strongest driver of venture capital investing. Private pension fund levels are a significant determinant over time but not across countries. Surprisingly, GDP and market capitalization growth are not significant. Government policies can have a strong impact, both by setting the regulatory stage, and by galvanizing investment during downturns. Finally, we also show that different types of venture capital financing are affected differently by these factors. In particular, early stage venture capital investing is negatively impacted by labor market rigidities, while later stage is not. IPOs have no effect on early stage venture capital investing across countries, but are a significant determinant of later stage venture capital investing across countries. Finally, government funded venture capital has different sensitivities to the determinants of venture capital than non-government funded venture capital. Our insights emphasize the need for a more differentiated approach to venture capital, both from a research as well as from a policy perspective. We feel that while later stage venture capital investing is well understood, early stage and government funded investments still require more extensive research.